FAKTOR RESIKO TERJADINNYA OBESITAS PADA SISWA TAMAN KANAK-KANAK RAUDHATUL ATHFAL AL MOURKI - M. Anas Anasiru; Wiwi Ulfairah Sutarno (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2016)
ABSTRACT Overweight and obesity occur due to higher energy intake than the energy released. High energy intake is caused by consumption of high-energy food sources and fats, while low energy consumption is caused by lack of physical activity and sedentary life style. (Minarto, 2011)This study aims to determine the risk factors for obesity in Raudhatul Athfal Almourky kindergarten students in Gorontalo RegencyThe method of this study included the type of analytical survey research. The population of 82 children and 15 children was sampled. The independent variables are risk factors including diet, and physical activity. Variable bound is Obesity in kindergarten students. Data analysis in this study used the